Amino-modified titanium carbide loaded transition metal composite catalyst as well as preparation method and application thereof
By introducing amino groups on the titanium carbide support and supporting transition metals to form a composite catalyst, the problem of insufficient activity of the existing catalyst is solved, and efficient catalytic and good cycle performance of ammonia borane hydrolysis is achieved.
Patent Information
- Application Number
- CN202411660682.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
AI Technical Summary
The catalytic activity of existing transition metal-based catalysts on ammonia borane hydrolysis needs to be further improved, and the rarity and cost of precious metal catalysts limit their industrial applications.
The amino group is used to modify the composite catalyst of titanium carbide-supported transition metal, and the hydrophilicity of the titanium carbide support is improved by introducing amino groups, and the support-metal synergy is induced to optimize the catalytic activity.
The catalytic activity and stability of the catalyst are improved, the rapid hydrolysis of ammonia borane is promoted, and high-purity hydrogen is generated, and excellent circulation performance is shown in the ammonia borane hydrolysis reaction.
Smart Images

Figure CN119500204A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalytic hydrogen production, and in particular to an amino-modified titanium carbide transition metal-loaded composite catalyst and a preparation method and application thereof. Background Art
[0002] At present, the development of clean and sustainable alternative energy is very important to alleviate the consumption of fossil fuels. Among various sustainable energy sources, hydrogen is considered to be a green energy with great application prospects. Therefore, safe and efficient control of hydrogen storage / release technology is crucial, and liquid phase hydrogen storage technology has attracted widespread attention due to its excellent safety and convenience. Ammonia borane (NH3BH3) has excellent hydrogen storage capacity (19.6%), is non-toxic and easy to transport, and is considered to be a reliable liquid phase hydrogen storage carrier. Under the action of a suitable catalyst, ammonia borane hydrolyzes (NH3BH3+2H2O→NH4 + +BO2 - +3H2) can quickly generate high-purity hydrogen and can be directly used in hydrogen fuel cells.
[0003] Precious metal-based catalysts can effectively promote the hydrolysis of ammonia borane to produce hydrogen, and have high TOF values and excellent stability. However, due to the rarity and high cost of precious metals, the industrial application of precious metal catalysts is inevitably hindered. Transition metals exhibit structural characteristics similar to those of precious metals. Therefore, transition metals (Ni, Co, Cu) are expected to become emerging materials to replace precious metal catalysts. However, the catalytic activity of transition metal-based catalysts for the hydrolysis of ammonia borane needs to be further improved. Summary of the invention
[0004] The purpose of the present invention is to provide an amino-modified titanium carbide transition metal-loaded composite catalyst and a preparation method and application thereof in view of the deficiencies in the prior art.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing an amino-modified titanium carbide-loaded transition metal composite catalyst, comprising the following steps:
[0007] (1) dispersing titanium carbide in water to obtain a titanium carbide solution;
[0008] mixing p-phenylenediamine with acetone to obtain an acetone solution of p-phenylenediamine;
[0009] (2) adding a p-phenylenediamine acetone solution dropwise to a titanium carbide solution to obtain amino-modified titanium carbide;
[0010] (3) dispersing the amino-modified titanium carbide in water to obtain an amino-modified titanium carbide solution;
[0011] (4) Mixing transition metal nitrate, sodium borohydride and amino-modified titanium carbide solution to obtain an amino-modified titanium carbide-loaded transition metal composite catalyst.
[0012] Preferably, in the titanium carbide solution of step (1), the mass volume ratio of titanium carbide to water is 0.5-2 mg:1 mL; the mass volume ratio of p-phenylenediamine to acetone is 50-80 mg:1 mL; and the mass ratio of titanium carbide to p-phenylenediamine is 1:4-8.
[0013] Preferably, the dripping rate in step (2) is 10 to 60 seconds per drop.
[0014] Preferably, in the amino-modified titanium carbide solution of step (3), the mass volume ratio of amino-modified titanium carbide to water is 1-3 mg:1 mL.
[0015] Preferably, the transition metal in the transition metal nitrate of step (4) comprises copper and cobalt, and the molar ratio of copper to cobalt is 1:1.5-4; the molar mass ratio of the transition metal nitrate to the amino-modified titanium carbide of step (3) is 0.1-0.2 mmol:15 mg; and the molar mass ratio of the transition metal nitrate to sodium borohydride is 0.1-0.2 mmol:30-50 mg.
[0016] Preferably, the method for preparing titanium carbide in step (1) comprises the following steps:
[0017] Titanium carbide is obtained by mixing titanium aluminum carbide, lithium fluoride and hydrochloric acid and etching.
[0018] Preferably, the mass volume ratio of the titanium aluminum carbide, lithium fluoride and hydrochloric acid is 1 g: 1-2 g: 10-20 mL, and the concentration of the hydrochloric acid is 6-11 mol / L.
[0019] Preferably, the etching temperature is 30-40° C., and the etching time is 18-30 hours.
[0020] The invention also provides an amino-modified titanium carbide transition metal-loaded composite catalyst prepared by the preparation method.
[0021] The present invention also provides the use of the amino-modified titanium carbide transition metal-loaded composite catalyst in the production of hydrogen by hydrolysis of ammonia borane.
[0022] The beneficial effects of the present invention include the following:
[0023] The invention introduces amino groups, which, on the one hand, effectively improve the hydrophilicity of the titanium carbide carrier, facilitate the formation of metal nanoparticles, and stabilize the dispersibility of the nanocatalytic system; on the other hand, can induce a strong carrier-metal synergistic effect, adjust the local electronic structure related to the electronic energy level near the active site, optimize the d-bond center and the Fermi level, thereby optimizing the adsorption / desorption behavior; the amino group can also serve as a proton scavenger to promote the dissociation of the OH bond in the water molecule, thereby generating faster reaction kinetics, accelerating the hydrolysis of ammonia borane, and improving the catalytic activity of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope image of the amino-modified titanium carbide-loaded transition metal composite catalyst prepared in Example 1;
[0025] Figure 2 A high-resolution transmission electron microscopy image of the amino-modified titanium carbide-loaded transition metal composite catalyst prepared in Example 1;
[0026] Figure 3 Cu 2p X-ray photoelectron spectrum of the amino-modified titanium carbide-loaded transition metal composite catalyst prepared in Example 1;
[0027] Figure 4 The Co 2p X-ray photoelectron spectrum of the amino-modified titanium carbide-supported transition metal composite catalyst prepared in Example 1;
[0028] Figure 5 The Ni 1s X-ray photoelectron spectrum of the amino-modified titanium carbide-loaded transition metal composite catalyst prepared in Example 1;
[0029] Figure 6 Ti3C2, PDA-Ti3C2 and Cu prepared in Example 1 0.2 Co 0.8 Fourier transform infrared spectrum of / PDA-Ti3C2;
[0030] Figure 7 Ti3C2, PDA-Ti3C2 and Cu prepared in Example 1 0.2 Co 0.8 Raman spectrum of / PDA-Ti3C2;
[0031] Figure 8 The amount of hydrogen produced by the composite catalyst of Example 1 and Comparative Examples 1 to 3 in the hydrogen production reaction by hydrolysis of ammonia borane;
[0032] Fig. 9 The amount of hydrogen produced by the composite catalysts of Examples 1 to 3 and Comparative Examples 4 to 7 when used in the hydrogen production reaction of ammonia borane hydrolysis;
[0033] Fig.10 The test results of the cycle performance of the amino-modified titanium carbide-loaded transition metal composite catalyst prepared in Example 1;
[0034] Fig.11 The diagram is a catalytic mechanism diagram of the amino-modified titanium carbide-loaded transition metal composite catalyst of the present invention in the hydrogen production reaction by hydrolysis of ammonia borane. DETAILED DESCRIPTION
[0035] The present invention provides a method for preparing an amino-modified titanium carbide-loaded transition metal composite catalyst, comprising the following steps:
[0036] (1) dispersing titanium carbide in water to obtain a titanium carbide solution;
[0037] mixing p-phenylenediamine with acetone to obtain an acetone solution of p-phenylenediamine;
[0038] (2) adding a p-phenylenediamine acetone solution dropwise to a titanium carbide solution to obtain amino-modified titanium carbide;
[0039] (3) dispersing the amino-modified titanium carbide in water to obtain an amino-modified titanium carbide solution;
[0040] (4) Mixing transition metal nitrate, sodium borohydride and amino-modified titanium carbide solution to obtain an amino-modified titanium carbide-loaded transition metal composite catalyst.
[0041] In the present invention, in the titanium carbide solution of step (1), the mass volume ratio of titanium carbide to water is preferably 0.5-2 mg:1 mL, and more preferably 0.9-1.5 mg:1 mL; the mass volume ratio of p-phenylenediamine to acetone is preferably 50-80 mg:1 mL, and more preferably 60-70 mg:1 mL, and more preferably 65 mg:1 mL; the mass ratio of titanium carbide to p-phenylenediamine is preferably 1:4-8, and more preferably 1:5-7, and more preferably 1:6.
[0042] In the present invention, the dispersion in step (1) is preferably ultrasonic dispersion, and the frequency of ultrasonic dispersion is preferably 70 to 90 kHz, more preferably 80 kHz; the time of ultrasonic dispersion is preferably 2 to 3 hours, more preferably 2.5 hours.
[0043] In the present invention, the dripping rate in step (2) is preferably 10 to 60 seconds per drop, more preferably 20 to 50 seconds per drop, and more preferably 30 seconds per drop.
[0044] In the present invention, after the dropwise addition in step (2) is completed, a mixed solution is obtained, and the mixed solution is preferably stirred, filtered, and dried in sequence to obtain amino-modified titanium carbide; the stirring speed is preferably 400-800 r / min, and more preferably 600 r / min; the stirring time is preferably 20-28 h, and more preferably 24 h; the filtration pressure is preferably -0.06-0.03 MPa, and more preferably -0.05 MPa; the filtration time is preferably 20-50 min, and more preferably 30 min; the drying is preferably vacuum drying, and the vacuum degree of vacuum drying is preferably -0.1-0.08 MPa, and more preferably -0.09 MPa; the vacuum drying time is preferably 20-28 h, and more preferably 24 h; the vacuum drying temperature is preferably 25-35°C, and more preferably 30°C.
[0045] In the present invention, in the amino-modified titanium carbide solution of step (3), the mass volume ratio of amino-modified titanium carbide to water is preferably 1-3 mg:1 mL, more preferably 1.5-2.5 mg:1 mL, and more preferably 2 mg:1 mL.
[0046] In the present invention, the dispersion in step (3) is preferably ultrasonic dispersion, and the frequency of ultrasonic dispersion is preferably 70 to 90 kHz, more preferably 80 kHz; the time of ultrasonic dispersion is preferably 20 to 40 min, more preferably 30 min.
[0047] In the present invention, the transition metal in the transition metal nitrate of step (4) preferably comprises copper and cobalt, and the molar ratio of copper to cobalt is preferably 1:1.5-4, more preferably 1:2-3.5, and more preferably 1:2.3-3; the molar mass ratio of the transition metal nitrate to the amino-modified titanium carbide of step (3) is preferably 0.1-0.2 mmol:15 mg, more preferably 0.12-0.18 mmol:15 mg, and more preferably 0.14-0.16 mmol:15 mg; the molar mass ratio of the transition metal nitrate to sodium borohydride is preferably 0.1-0.2 mmol:30-50 mg, more preferably 0.12-0.18 mmol:35-45 mg, and more preferably 0.14-0.16 mmol:40 mg.
[0048] In the present invention, the role of sodium borohydride is to promote the copper and cobalt nanoparticles to be loaded on the amino-modified titanium carbide.
[0049] In the present invention, after the mixing in step (4), centrifugation and drying are preferably performed in sequence to obtain an amino-modified titanium carbide loaded transition metal composite catalyst; the centrifugal speed is preferably 4000-8000 r / min, and more preferably 6000 r / min; the centrifugal time is preferably 2-5 min, and more preferably 3 min; the drying is preferably vacuum drying, and the vacuum degree of vacuum drying is preferably -0.1-0.08 MPa, and more preferably -0.09 MPa; the vacuum drying time is preferably 12-36 h, and more preferably 24 h; the vacuum drying temperature is preferably 25-35°C, and more preferably 30°C.
[0050] In the present invention, the method for preparing titanium carbide in step (1) preferably comprises the following steps:
[0051] Titanium carbide is obtained by mixing titanium aluminum carbide, lithium fluoride and hydrochloric acid and etching.
[0052] In the present invention, the mass volume ratio of the titanium aluminum carbide, lithium fluoride and hydrochloric acid is preferably 1g:1-2g:10-20mL, further preferably 1g:1.3-1.8g:13-18mL, and more preferably 1g:1.6g:16mL; the concentration of hydrochloric acid is preferably 6-11mol / L, further preferably 6.75-10mol / L, and more preferably 7-9mol / L.
[0053] In the present invention, preferably, lithium fluoride and hydrochloric acid are first mixed to obtain an intermediate solution, and then titanium aluminum carbide is added to the intermediate solution; stirring is preferably performed during the mixing process, and the stirring speed is preferably 300 to 500 r / min, and more preferably 400 r / min, and stirring is stopped when the lithium fluoride is completely dissolved; the process of adding titanium aluminum carbide is preferably carried out in an ice bath.
[0054] In the present invention, the etching temperature is preferably 30 to 40° C., more preferably 33 to 38° C., and more preferably 35° C.; the etching time is preferably 18 to 30 h, more preferably 20 to 28 h, and more preferably 24 h.
[0055] In the present invention, after the etching is completed, washing and drying are preferably carried out in sequence to obtain titanium carbide; the reagent used for the washing is preferably water, and the washing is completed when the washing liquid is neutral; the drying is preferably vacuum drying, and the vacuum degree of the vacuum drying is preferably -0.1 to -0.08 MPa, and more preferably -0.09 MPa; the vacuum drying time is preferably 12 to 36 hours, and more preferably 24 hours; the vacuum drying temperature is preferably 25 to 35°C, and more preferably 30°C.
[0056] The invention also provides an amino-modified titanium carbide transition metal-loaded composite catalyst prepared by the preparation method.
[0057] The present invention also provides the use of the amino-modified titanium carbide transition metal-loaded composite catalyst in the production of hydrogen by hydrolysis of ammonia borane.
[0058] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0059] Example 1
[0060] 7.5 mL of 9 mol / L hydrochloric acid, 2.5 mL of deionized water and 0.8 g of lithium fluoride were mixed and stirred at 400 r / min until the lithium fluoride was completely dissolved to obtain an intermediate solution. The intermediate solution was placed in an ice bath, 0.5 g of titanium aluminum carbide was added to the intermediate solution, and the solution was etched at 35°C for 24 hours. After etching, the solution was washed with deionized water until the washing solution was neutral, and then dried at 30°C and a vacuum degree of -0.1 MPa for 24 hours to obtain titanium carbide (Ti3C2).
[0061] 45 mg of titanium carbide was dispersed in 50 mL of deionized water and ultrasonically treated at a frequency of 80 kHz for 2.5 h to obtain a titanium carbide solution. 270 mg of p-phenylenediamine was dissolved in 4.5 mL of acetone to obtain an acetone solution of p-phenylenediamine. The acetone solution of p-phenylenediamine was added dropwise to the titanium carbide solution at a rate of 30 seconds per drop to obtain a mixed solution. The mixed solution was stirred at a speed of 600 r / min for 24 h, then filtered at -0.05 MPa for 30 min, and then dried at 30 ° C and a vacuum degree of -0.1 MPa for 24 h to obtain amino-modified titanium carbide (PDA-Ti3C2).
[0062] 15 mg of amino-modified titanium carbide was dispersed in 7.5 mL of deionized water and ultrasonically treated at a frequency of 80 kHz for 30 min to obtain an amino-modified titanium carbide solution. 0.032 mmol of copper nitrate hexahydrate and 0.128 mmol of cobalt nitrate trihydrate were added to the amino-modified titanium carbide solution, and then 50 mg of sodium borohydride was added to obtain a mixed solution. The mixed solution was centrifuged at a speed of 6000 r / min for 3 min, and the centrifugal product was dried at 30°C and a vacuum degree of -0.1 MPa for 24 h to obtain an amino-modified titanium carbide-loaded transition metal composite catalyst.
[0063] The amino-modified titanium carbide-loaded transition metal composite catalyst prepared in this example is marked as Cu 0.2 Co 0.8 / PDA-Ti3C2.
[0064] Figure 1 This is a scanning electron microscope image of the amino-modified titanium carbide-loaded transition metal composite catalyst prepared in Example 1. Figure 1It can be seen that Cu 0.2 Co 0.8 / PDA-Ti3C2 exhibits a prominent interstitial layered structure, which provides a larger surface area for metal nanoparticles and enables more complete contact between active sites and reactants, promoting the improvement of catalytic activity.
[0065] Figure 2 This is a high-resolution transmission electron microscopy image of the amino-modified titanium carbide-loaded transition metal composite catalyst prepared in Example 1. Figure 2 It can be seen that Cu 0.2 Co 0.8 / PDA-Ti3C2 introduced amino groups to make Cu and Co particles with a size of about 1.8 nm dispersed more evenly on the Ti3C2 surface; the spacing between the Co (111) crystal plane and the Cu (200) crystal plane was 0.19 nm, which further confirmed the formation of CuCo nanoparticles.
[0066] Figure 3 The Cu 2p X-ray photoelectron spectrum of the amino-modified titanium carbide-loaded transition metal composite catalyst prepared in Example 1. Figure 3 It can be seen that the main peaks at 931.5eV and 951.4eV belong to Cu 0 2p 3 / 2 and Cu 0 2p 1 / 2 , and the corresponding satellite peaks are located at 940.7 eV and 959.5 eV, respectively.
[0067] Figure 4 This is the Co 2p X-ray photoelectron spectrum of the amino-modified titanium carbide-loaded transition metal composite catalyst prepared in Example 1. Figure 4 It can be seen that the main peaks at 777.9 eV and 793.8 eV belong to Co 0 2p 3 / 2 and Co 0 2p 1 / 2 , and the corresponding satellite peaks are located at 783.4 eV and 799.8 eV, respectively.
[0068] Figure 5 This is the Ni 1s X-ray photoelectron spectrum of the amino-modified titanium carbide-supported transition metal composite catalyst prepared in Example 1. As shown in Figure 5, the N 1s peak can be divided into two different binding energy components: one is located at 399.1 eV, which is characteristic of amine and amide groups; the other is located at 397.9 eV, corresponding to pyridine nitrogen.
[0069] Figure 6 Ti3C2, PDA-Ti3C2 and Cu prepared in Example 1 0.2 Co 0.8Fourier transform infrared spectrum of / PDA-Ti3C2. Figure 6 It can be seen that the Ti3C2 support is at 2922cm -1 and 2852cm -1 There are two adsorption peaks at 3425 cm-1, while the vibration adsorption peaks of -OH, Ti-O and CF appear at 3425 cm-1, -1 、1623cm -1 and 1092cm -1 At 3340cm -1 、1598cm -1 and 890cm -1 In addition to the symmetric stretching vibration peak corresponding to NH, the bending band of NH, and the bending vibration peak of NH, most of the other characteristic peaks of the Ti3C2 support still exist. -1 and 1115cm -1 There are stretching vibration peaks of aromatic C=CN at the positions of the two atoms, respectively. This result indicates that PDA containing -NH2 groups is successfully grafted onto the Ti3C2 surface.
[0070] Figure 7 Ti3C2, PDA-Ti3C2 and Cu prepared in Example 1 0.2 Co 0.8 Raman spectrum of / PDA-Ti3C2. Figure 7 It can be seen that with the addition of PDA, the original Ti3C2 structure is still retained.
[0071] Example 2
[0072] The amount of copper nitrate hexahydrate used in Example 1 was modified to 0.064 mmol, the amount of cobalt nitrate trihydrate used was modified to 0.096 mmol, and the rest was the same as in Example 1.
[0073] The amino-modified titanium carbide-loaded transition metal composite catalyst prepared in this example is marked as Cu 0.4 Co 0.6 / PDA-Ti3C2.
[0074] Example 3
[0075] The amount of copper nitrate hexahydrate in Example 1 was modified to 0.048 mmol, the amount of cobalt nitrate trihydrate was modified to 0.112 mmol, and the rest was the same as in Example 1.
[0076] The amino-modified titanium carbide-loaded transition metal composite catalyst prepared in this example is marked as Cu 0.3 Co 0.7 / PDA-Ti3C2.
[0077] Example 4
[0078] 8 mL of 10 mol / L hydrochloric acid and 1 g of lithium fluoride were mixed, and stirred at a speed of 500 r / min until the lithium fluoride was completely dissolved to obtain an intermediate solution. The intermediate solution was placed in an ice bath, 0.5 g of titanium aluminum carbide was added to the intermediate solution, and the solution was etched at 40°C for 18 hours. After the etching was completed, it was washed with deionized water until the washing solution was neutral, and then dried at 35°C and a vacuum degree of -0.08 MPa for 36 hours to obtain titanium carbide.
[0079] 90 mg of titanium carbide was dispersed in 45 mL of deionized water and ultrasonically treated at a frequency of 90 kHz for 2 h to obtain a titanium carbide solution. 360 mg of p-phenylenediamine was dissolved in 4.5 mL of acetone to obtain an acetone solution of p-phenylenediamine. The acetone solution of p-phenylenediamine was added dropwise to the titanium carbide solution at a rate of 50 seconds per drop to obtain a mixed solution. The mixed solution was stirred at a speed of 800 r / min for 20 h, then filtered at -0.03 MPa for 50 min, and then dried at 35 ° C and a vacuum degree of -0.08 MPa for 20 h to obtain amino-modified titanium carbide.
[0080] 15 mg of amino-modified titanium carbide was dispersed in 5 mL of deionized water and ultrasonically treated at a frequency of 90 kHz for 20 min to obtain an amino-modified titanium carbide solution. 0.022 mmol of copper nitrate hexahydrate and 0.078 mmol of cobalt nitrate trihydrate were added to the amino-modified titanium carbide solution, and then 30 mg of sodium borohydride was added to obtain a mixed solution. The mixed solution was centrifuged at a speed of 4000 r / min for 5 min, and the centrifugal product was dried at 35°C and a vacuum degree of -0.08 MPa for 36 h to obtain an amino-modified titanium carbide-loaded transition metal composite catalyst.
[0081] Example 5
[0082] Mix 6.5 mL of 9 mol / L hydrochloric acid and 0.5 g of lithium fluoride, stir at 300 r / min until the lithium fluoride is completely dissolved to obtain an intermediate solution. Place the intermediate solution in an ice bath, add 0.5 g of titanium aluminum carbide to the intermediate solution, place it at 30°C for etching for 30 hours, wash it with deionized water after etching until the washing liquid is neutral, and then dry it at 25°C and a vacuum degree of -0.09 MPa for 12 hours to obtain titanium carbide.
[0083] Disperse 43.75 mg of titanium carbide in 30 mL of deionized water and treat with ultrasound at a frequency of 70 kHz for 3 hours to obtain a titanium carbide solution. Dissolve 350 mg of p-phenylenediamine in 5 mL of acetone to obtain an acetone solution of p-phenylenediamine. Add the acetone solution of p-phenylenediamine to the titanium carbide solution at a rate of 20 seconds per drop to obtain a mixed solution. Stir the mixed solution at a speed of 400 r / min for 28 hours, then filter at -0.06 MPa for 20 minutes, and then dry at 25°C and a vacuum degree of -0.09 MPa for 28 hours to obtain amino-modified titanium carbide.
[0084] 15 mg of amino-modified titanium carbide was dispersed in 15 mL of deionized water, and ultrasonic treatment was performed at a frequency of 70 kHz for 40 min to obtain an amino-modified titanium carbide solution. 0.05 mmol of copper nitrate hexahydrate and 0.15 mmol of cobalt nitrate trihydrate were added to the amino-modified titanium carbide solution, and then 40 mg of sodium borohydride was added to obtain a mixed solution. The mixed solution was centrifuged at a speed of 8000 r / min for 2 min, and the centrifugal product was dried at 25°C and a vacuum degree of -0.1 MPa for 12 h to obtain an amino-modified titanium carbide-loaded transition metal composite catalyst.
[0085] Comparative Example 1
[0086] 7.5 mL of 9 mol / L hydrochloric acid, 2.5 mL of deionized water and 0.8 g of lithium fluoride were mixed and stirred at 400 r / min until the lithium fluoride was completely dissolved to obtain an intermediate solution. The intermediate solution was placed in an ice bath, 0.5 g of titanium aluminum carbide was added to the intermediate solution, and the solution was etched at 35°C for 24 hours. After the etching was completed, the solution was washed with deionized water until the washing solution was neutral, and then dried at 30°C and a vacuum degree of -0.1 MPa for 24 hours to obtain titanium carbide.
[0087] 15 mg of titanium carbide was dispersed in 7.5 mL of deionized water and ultrasonically treated at a frequency of 80 kHz for 30 min to obtain a titanium carbide solution. 0.032 mmol of copper nitrate hexahydrate and 0.128 mmol of cobalt nitrate trihydrate were added to the titanium carbide solution, and then 50 mg of sodium borohydride was added to obtain a mixed solution. The mixed solution was centrifuged at a speed of 6000 r / min for 3 min, and the centrifugal product was dried at 30°C and a vacuum degree of -0.1 MPa for 24 h to obtain a composite catalyst of titanium carbide loaded with transition metals.
[0088] Comparative Example 2
[0089] The amount of p-phenylenediamine in Example 1 was modified to 135 mg, and the rest was the same as in Example 1.
[0090] Comparative Example 3
[0091] The amount of p-phenylenediamine in Example 1 was modified to 540 mg, and the rest was the same as in Example 1.
[0092] Comparative Example 4
[0093] The amount of copper nitrate hexahydrate in Example 1 was modified to 0.016 mmol, the amount of cobalt nitrate trihydrate was modified to 0.144 mmol, and the rest was the same as in Example 1.
[0094] The amino-modified titanium carbide-loaded transition metal composite catalyst prepared in this comparative example is marked as Cu 0.1 Co 0.9 / PDA-Ti3C2.
[0095] Comparative Example 5
[0096] The amount of copper nitrate hexahydrate in Example 1 was modified to 0.096 mmol, the amount of cobalt nitrate trihydrate was modified to 0.064 mmol, and the rest was the same as in Example 1.
[0097] The amino-modified titanium carbide-loaded transition metal composite catalyst prepared in this comparative example is marked as Cu 0.6 Co 0.4 / PDA-Ti3C2.
[0098] Comparative Example 6
[0099] The copper nitrate hexahydrate in Example 1 is omitted, and the rest is the same as Example 1.
[0100] The amino-modified titanium carbide-loaded transition metal composite catalyst prepared in this comparative example is marked as Co / PDA-Ti3C2.
[0101] Comparative Example 7
[0102] The cobalt nitrate trihydrate in Example 1 is omitted, and the rest is the same as Example 1.
[0103] The amino-modified titanium carbide-loaded transition metal composite catalyst prepared in this comparative example is marked as Cu / PDA-Ti3C2.
[0104] The composite catalysts of Examples 1 to 3 and Comparative Examples 1 to 7 were respectively used to catalyze the hydrolysis reaction of ammonia borane, and the specific steps were as follows: 0.02 g of the composite catalyst was placed in a double-necked flask, the double-necked flask was transferred to a 50° C. water bath, and a wet gas flowmeter was connected. 2 mmol of ammonia borane and 0.5 mL of deionized water were added to the double-necked flask, and a hydrogen release test was performed. The test was stopped when the collection reading of the wet gas flowmeter did not change within 1 min, and the time required for hydrogen release to end and the volume of hydrogen were recorded.
[0105] Figure 8The hydrogen production of the composite catalysts of Example 1 and Comparative Examples 1 to 3 for the hydrogen production reaction by hydrolysis of ammonia borane. Figure 8 It can be seen that with the increase of the dosage of p-phenylenediamine, the catalytic kinetics of the composite catalyst for the hydrogen production reaction of ammonia borane hydrolysis is enhanced, and the maximum hydrogen production is achieved when the dosage of p-phenylenediamine is 270 mg (the catalytic activity at this time reaches 71.8 mol H2 mol cat - 1 min -1 ); Continue to increase the dosage of p-phenylenediamine, excessive p-phenylenediamine will block the catalytic sites, thereby reducing the catalytic efficiency.
[0106] Fig. 9 The amount of hydrogen produced by the composite catalysts of Examples 1 to 3 and Comparative Examples 4 to 7 when used in the hydrogen production reaction of ammonia borane hydrolysis. Fig. 9 It can be seen that the catalytic activity of the Cu and Co bimetallic supported catalyst is significantly better than that of the single metal supported catalyst; the molar ratio of Cu / Co has a significant effect on the hydrogen production reaction of ammonia borane hydrolysis and needs to be strictly controlled; the Cu prepared in Example 1 0.2 Co 0.8 / PDA-Ti3C2 has excellent catalytic performance, releasing 138mL of hydrogen in 0.5min of reaction, and the catalytic activity can reach 71.8mol H2 mol cat -1 min -1 ; With the increase of Cu content, the kinetics of the hydrogen production reaction of ammonia borane hydrolysis decreased, such as the Cu in Example 2 0.4 Co 0.6 / PDA-Ti3C2; If the Cu content continues to increase, the kinetics of the hydrogen production reaction of ammonia borane hydrolysis will be significantly reduced. For example, the Cu 0.6 Co 0.4 / PDA-Ti3C2. This volcano-shaped catalytic kinetics shows that transition metals have a synergistic effect in composite catalysts. By adjusting the Cu / Co molar ratio, the surface electronic state and lattice compression of the bimetallic Cu and Co nanosystems can be effectively adjusted, and the local strain and electronic configuration of the surface catalytic sites can be further optimized, thus rapidly improving the kinetics of hydrogen production by hydrolysis of ammonia borane.
[0107] The amino-modified titanium carbide-loaded transition metal composite catalyst prepared in Example 1 was subjected to a cyclic performance test of ammonia borane hydrolysis hydrogen production reaction, and the test steps were as follows: after the first ammonia borane hydrolysis reaction, the composite catalyst was taken out, washed with 20 mL of deionized water, and then centrifuged at a speed of 6000 r / min for 3 min, the supernatant was discarded to obtain the composite catalyst after the first reaction, and the composite catalyst was further subjected to the above-mentioned ammonia borane hydrolysis reaction. The above steps were repeated.
[0108] Fig.10 The test results of the cycle performance of the amino-modified titanium carbide-loaded transition metal composite catalyst prepared in Example 1 are as follows. Fig.10 It can be seen that after 5 reaction cycles, the Cu 0.2 Co 0.8 / PDA-Ti3C2 can still stably maintain its kinetic activity and has 100% selectivity for hydrogen production from the hydrolysis of ammonia borane. This result shows that the introduction of p-phenylenediamine can effectively stabilize Cu and Co nanoparticles through the optimal electronegativity of the amino group and inhibit the aggregation of Cu and Co nanoparticles during the hydrolysis of ammonia borane.
[0109] Fig.11 The figure is a catalytic mechanism diagram of the amino-modified titanium carbide-loaded transition metal composite catalyst in the ammonia borane hydrolysis hydrogen production reaction. Fig.11 It can be seen that in the initial stage of the reaction, -NH2 acts as a proton scavenger, which can stretch water molecules and promote the deprotonation of water, quickly forming H2NH* and CuCo-NH3BH3, which is the determining step for the rate of the entire ammonia borane hydrolysis hydrogen production reaction. Subsequently, the "electron-rich" configuration formed by CuCo nanoparticles can activate and cut the BN bond in BH3NH3 to form BH3OH* (BH3NH3+OH*→BH3OH*+NH3*). BH3OH* is a key intermediate in the ammonia borane hydrolysis hydrogen production reaction. Due to the low thermodynamic level, the unstable BH3OH* is deprotonated by -H2NH* to form BH2OH* (BH3OH*→BH2OH*+H*). Next, the electrostatic interaction between the B atom and the N atom reduces the barrier for the recombination of the BN bond, thereby producing BH2OH-NH3 (BH2OH*+NH3*→BH2OH-NH3). At the same time, two H2NH* combine with each other to generate H2 molecules far away from the catalyst surface. Similar conversion reactions are then carried out: BH2OH-NH3+H2O→BH(OH)2-NH3+H2, BH(OH)2-NH3+H2O→
[0110] B(OH)3-NH3+H2, finally produces 3 equal H2 molecules. Among them, * represents the adsorption state of the substance.
[0111] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an amino-modified titanium carbide-loaded transition metal composite catalyst, characterized in that: The following steps are included: (1) dispersing titanium carbide in water to obtain a titanium carbide solution; mixing p-phenylenediamine with acetone to obtain an acetone solution of p-phenylenediamine; (2) adding a p-phenylenediamine acetone solution dropwise to a titanium carbide solution to obtain amino-modified titanium carbide; (3) dispersing the amino-modified titanium carbide in water to obtain an amino-modified titanium carbide solution; (4) Mixing transition metal nitrate, sodium borohydride and amino-modified titanium carbide solution to obtain an amino-modified titanium carbide-loaded transition metal composite catalyst.
2. The preparation method according to claim 1, characterized in that: In the titanium carbide solution of step (1), the mass volume ratio of titanium carbide to water is 0.5-2 mg:1 mL; the mass volume ratio of p-phenylenediamine to acetone is 50-80 mg:1 mL; and the mass ratio of titanium carbide to p-phenylenediamine is 1:4-8.
3. The preparation method according to claim 1 or 2, characterized in that: The dripping rate of step (2) is 10 to 60 seconds per drop.
4. The preparation method according to claim 3, characterized in that: In the amino-modified titanium carbide solution of step (3), the mass volume ratio of amino-modified titanium carbide to water is 1-3 mg:1 mL.
5. The preparation method according to claim 4, characterized in that: The transition metal in the transition metal nitrate of step (4) comprises copper and cobalt, and the molar ratio of copper to cobalt is 1:1.5-4; the molar mass ratio of the transition metal nitrate to the amino-modified titanium carbide of step (3) is 0.1-0.2 mmol:15 mg; the molar mass ratio of the transition metal nitrate to sodium borohydride is 0.1-0.2 mmol:30-50 mg.
6. The preparation method according to claim 4 or 5, characterized in that: The method for preparing titanium carbide in step (1) comprises the following steps: Titanium carbide is obtained by mixing titanium aluminum carbide, lithium fluoride and hydrochloric acid and etching.
7. The preparation method according to claim 6, characterized in that: The mass volume ratio of the titanium aluminum carbide, lithium fluoride and hydrochloric acid is 1g:1-2g:10-20mL, and the concentration of the hydrochloric acid is 6-11 mol / L.
8. The preparation method according to claim 7, characterized in that: The etching temperature is 30-40° C., and the etching time is 18-30 hours.
9. The amino-modified titanium carbide-loaded transition metal composite catalyst prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the amino-modified titanium carbide transition metal-loaded composite catalyst according to claim 9 in hydrogen production by hydrolysis of ammonia borane.